IOL Power Calculation Features after Radial Keratotomy - A. A. Kasyanov; E. G. Ryzhkova (Oftalʹmologiâ)
IOL power calculation after keratorefractive surgery is an important applied aspect of cataract surgery. The probability of refractive error is especially high when calculating in patients with a history of radial keratotomy. There is no unified approach to the tactics and methodology of calculation for this category of patients at the moment. The studies were conducted in a group of 17 patients (26 eyes) with a history of RK. The Haigis formula, which does not use keratometry to predict ELP, was chosen as the main one for the calculation. IOL calculation and biometrics were carried out on the IOL-Master, but corrected TCP IOL (Ray Traced) data obtained on the Galilei keratotomograph were manually entered into the optional keratometry fields. Thу Burrett True-K and Hoffer Q were used as verification formulas, the calculation was also carried out on IOL-Master, using corrected Galilei data. In all cases, postoperative refraction close to emmetropic was obtained. The spherical component of refraction ranged from +0.5 to -1.0 D, cylindrical — from 0.0 to 4.0 D, according to autorefractometry. Visual acuity without correction ranged from 0.4 to 1.0. Uncorrected visual acuity of 0.8 and higher was obtained in 65.38% of cases. The calculation algorithm implemented by us using the Haigis formula in combination with the use of individually adjusted keratometric TCP IOL data (Ray Traced, Galilei), allowed us to significantly improve the accuracy of IOL power calculating in patients with a history of RK and achieve target refraction even in cases of complex and irregular corneal topography.